2017
DOI: 10.5114/aoms.2017.67283
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes in children with chronic kidney disease stage 5 over the last 40 years

Abstract: IntroductionWe evaluated outcomes in children with chronic kidney disease stage 5 (CKD 5) treated in the first pediatric dialysis unit in Poland during 1973-2012.Material and methodsThe retrospective analysis included 208 children with CKD 5 undergoing renal replacement therapy (RRT), stratified into four decades of treatment: 1973–1982, 1983–1992, 1993–2002, and 2003–2012.ResultsThe most common causes of CKD 5 included glomerulonephritis in 27.4% and pyelonephritis secondary to urinary tract anomalies in 25.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…Death occurs in approximately 4.8 out of 100 children undergoing hemodialysis. 11 The mortality rate in our study was higher, at 16.3%. Some studies suggested the potential association between mortality and calcitriol levels.…”
Section: Discussioncontrasting
confidence: 50%
“…Death occurs in approximately 4.8 out of 100 children undergoing hemodialysis. 11 The mortality rate in our study was higher, at 16.3%. Some studies suggested the potential association between mortality and calcitriol levels.…”
Section: Discussioncontrasting
confidence: 50%
“…Thus, in an acute stage of AML, colonoscopy may detect the intestinal changes which could be associated with AML by the same logical approach. In differential diagnosis, anamnestic factors are also important; for example, when the abdominal pain of a patient with chronic renal failure is questioned, it is malpractice to try to make the AA or AML discrimination instead of performing dialysis-related tests immediately [26].…”
Section: Discussionmentioning
confidence: 99%
“…Year 2016 (as well as in the beginning of 2017) has been reallyinteresting in the field of kidney research; several important findings were reported in the field of glomerulopathies, diabetic nephropathy, and lupus nephritis but also in hemodialysis and renal transplantation [49][50][51][52][53][54][55][56][57][58][59][60][61][62]. It is obvious that for the current review we have selected only the most important ones in the authors' opinion.…”
Section: Kidney Update 2016mentioning
confidence: 99%